Disaster Risk Reduction and the Global System Ruminations on a Way Forward - Gordy, Michael (SpringerBriefs in Climate Studies,, 2016)
This short manuscript is both a distillation of some of the latest work on disaster risk reduction and an interpretation of this distillation from the author's political economic perspective. It is based on information found in the flagship reports on disaster risk reduction of the United Nations. The book sums up and interprets issues of disaster risk reduction and makes them accessible to professional and non-professional readers alike, including governmental policy makers.